Efficient Near‐Infrared Electroluminescence at 840 nm with "Metal‐Free" Small‐Molecule:Polymer Blends. Issue 34 (10th July 2018) - Minotto, Alessandro; Murto, Petri; Genene, Zewdneh; Zampetti, Andrea; Carnicella, Giuseppe; Mammo, Wendimagegn; Andersson, Mats R.; Wang, Ergang; Cacialli, Franco
Abstract: Due to the so‐called energy‐gap law and aggregation quenching, the efficiency of organic light‐emitting diodes (OLEDs) emitting above 800 nm is significantly lower than that of visible ones. Successful exploitation of triplet emission in phosphorescent materials containing heavy metals has been reported, with OLEDs achieving remarkable external quantum efficiencies (EQEs) up to 3.8% (peak wavelength > 800 nm). For OLEDs incorporating fluorescent materials free from heavy or toxic metals, however, we are not aware of any report of EQEs over 1% (again for emission peaking at wavelengths > 800 nm), even for devices leveraging thermally activated delayed fluorescence (TADF). Here, the development of polymer light‐emitting diodes (PLEDs) peaking at 840 nm and exhibiting unprecedented EQEs (in excess of 1.15%) and turn‐on voltages as low as 1.7 V is reported. These incorporate a novel triazolobenzothiadiazole‐based emitter and a novel indacenodithiophene‐based transport polymer matrix, affording excellent spectral and transport properties. To the best of knowledge, such values are the best ever reported for electroluminescence at 840 nm with a purely organic and solution‐processed active layer, not leveraging triplet‐assisted emission. Abstract : External quantum efficiency exceeding 1% is reported from near‐infrared (NIR) polymer light‐emitting diodes with emission peaked at 840 nm, originating from fluorescent materials. Such polymer light‐emitting diodes are based on a metal‐free and fully solution‐processed active layer, consisting of a novel triazolobenzothiadiazole‐based NIR fluorophore embedded in a novel indacenodithiophene‐based transport polymer matrix.